2018
DOI: 10.14302/issn.2577-2279.ijha-18-2221
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Significance of Basic Sciences for Clinical Studies

Abstract: Background: Faculty of Medicine and Health sciences at University of Kassala, Sudan was established 1990. It adopts the traditional curricula, which implemented in preclinical (basic sciences) and clinical phases. This study was held to explore students' perception and attitudes towards the basic sciences. Methods: A descriptive cross-sectional study was conducted during April- August 2017 among 251 medical students. Self-administered questionnaire was used to collect data. It was collected and analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…35 Only 26.8% of respondents could recall biochemistry during their clinical discussions, while 55.6% could recall physiology and 66.5% could recall anatomy. Our findings were in line with those of Gupta et al and Nuggedalla et al 18,36 Spencer et al also wrote in their paper that basic medical science retention was generally low, so they recommended to fully integrate basic medical sciences during the whole duration of a medical curriculum. 37 Instead of concentrating on ways to minimize knowledge loss, medical education program designers should concentrate on ways to increase the degree of knowledge development.…”
Section: Discussionsupporting
confidence: 92%
“…35 Only 26.8% of respondents could recall biochemistry during their clinical discussions, while 55.6% could recall physiology and 66.5% could recall anatomy. Our findings were in line with those of Gupta et al and Nuggedalla et al 18,36 Spencer et al also wrote in their paper that basic medical science retention was generally low, so they recommended to fully integrate basic medical sciences during the whole duration of a medical curriculum. 37 Instead of concentrating on ways to minimize knowledge loss, medical education program designers should concentrate on ways to increase the degree of knowledge development.…”
Section: Discussionsupporting
confidence: 92%
“…Such sciences are frequently preferred because they seamlessly mend the gap between practical skills and fundamental theory. Basic sciences such as anatomy, are of practical value during surgeries and surgical rounds, while pathology and physiology contribute to an essential understanding of diseases and are taught in a more clear fashion in the curriculum [ 18 ]. On the other hand, students believed that biochemistry and microbiology are the least useful in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…1 Negative sentiments towards the course are also shared by medical students in other parts of the globe. 4,5 Additionally, students in North America are faced with the course once again in the preclinical years of medical school, leading to redundancy allegations from students. 6 Biochemistry education often involves the description of a large volume of modern and contemporary researchled facts and figures.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding biochemistry specifically, a recent large‐scale study of students from 102 institutions reported that a semester of biochemistry may independently play a role in the further attrition of 15% of undergraduates, despite meeting all other course requirements 1 . Negative sentiments towards the course are also shared by medical students in other parts of the globe 4,5 . Additionally, students in North America are faced with the course once again in the preclinical years of medical school, leading to redundancy allegations from students 6 …”
Section: Introductionmentioning
confidence: 99%